Pojok Literasi Sebagai Program Pemberdayaan Masyarakat Dalam Upaya Membangun Desa Cerdas Di Desa Nagrog Csicalengka - Endah Megawati; Hernawati Hernawati; Amalia Amalia SR; Anggie Mauditya; Auliya Nuranis; Fadli Jihadul Islam; Fahmi Rahmah Astuty; Lulu Lutfiani (Universitas Lambung Mangkurat, 2023)
Indonesia has the lowest literacy rate in the world. It ranks 62 out of 70 countries that have made literacy part of the culture that lives and develops in society. This is due to the lack of understanding of the concept of literacy for Indonesians. The term literacy is something foreign that is not widely recognized, especially by rural communities who live in the interior of the mountain, allowing a lack of access to information obtained. The activities of reading, writing, discussing and being literate to the current situation are part of literacy. Nagrog village is located in the highlands of Bandung district, however facilities and infrastructure to support literacy activities are already available. However, there is no structured system in managing this potential. Thus, the PPK ORMAWA HIMA Islamic Religious Education Team of Muhammadiyah University Bandung together with the village government, community leaders and the community itself have the aim of re-empowering their potential so that they can help minimize educational inequality through the Literacy Corner program by participating in making the village community a smart village. The method used is the ABCD (Asset Based Community Development) method which focuses on community development by making the community the actors and determinants in efforts to develop a better environment.Keywords: Society, Potential, Literacy